What It Means to Be a Man How to Become a Better Person - Mullen, Bill (Marine Corps University Press (MCUP), 2023)
We all have flaws because, as humans, we are all inherently fallible. If we can focus on becoming better people in life, it will likely help mitigate that fallibility. What It Means to Be a Man focuses on the concept that if all young Marines internalize the words and thoughts here, and use them to not only be better Marines but more importantly, better people, then we can be a much better Service overall. The U.S. Marine Corps and the American people have invested so much time, effort, and money into them that they are more than worth the effort to make them better people now but also when they take off the uniform and return to civilian society.